The modifying role of pregnancy on ophthalmological and neuro-ophthalmological diseases - Henry Liu; Yiu-chia Chang; Xiang Ji (University of Ottawa Journal of Medicine, 2017)
The female visual system experiences a series of physiological modifications during pregnancy, and these changes have profound implications on many general ophthalmological and neuro-ophthalmological disorders, exacerbating some conditions while alleviating others. Patients with open-angle glaucoma experience improved disease states, with accompanying normal visual fields. Uveitis and MS-induced optic neuritis exhibit decreased rates of occurrence. Non-proliferative diabetic retinopathy initially worsens with gestation, eventually improving in the postpartum state with only 5% of cases progressing into the proliferative stage. As for idiopathic intracranial hypertension, existing symptoms worsen during pregnancy. Therapeutic interventions such as immunosuppressants, anti-neoplastic drugs, and steroids administered prophylactically during fetal development may lead to potential teratogenic outcomes manifesting in devastating birth defects and should be administered with caution.